Status and Prospect of Reclaimed Water Reuse in China - GUO Xingxing; LUO Huan; LI Ning (Renmin Zhujiang)
The shortage of water resources is the main obstacle to China's economic development,and the reuse of reclaimed water is an effective way to solve this problem.It is urgent to clarify the development status and existing problems of the reclaimed water industry in China,so as to achieve urban ecological and sustainable development.This study reviewed the policies,regulations,and standards of reclaimed water reuse in China and summarized the main ways to reuse reclaimed water.The development status and application examples of reclaimed water treatment technology were introduced,and future development was predicted.In summary,this paper put forward four suggestions for the reuse of reclaimed water in China:①perfecting the standards and specifications of reclaimed water reuse;②strengthening the transformation of the reclaimed water treatment process in sewage treatment plants;③establishing risk assessment system of reclaimed water;④intensifying the construction planning for the urban reclaimed water reuse.